Low-performing student responses to state merit scholarships - Christopher Erwin (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2019)
State merit scholarships may affect academic outcomes for low-performing college students, yet low-performers are generally overlooked in existing literature. New Mexico's lottery scholarship provides tuition-free college to residents meeting a uniquely "low-bar" eligibility criteria. Using administrative data, a discontinuity in eligibility rules identifies local average treatment effects on degree completion and course taking behavior for students with below-average college grades. Results suggest a reduction in time-to-degree corresponding to the scholarship's funding cap, with no overall change in degree completion. Despite modest eligibility requirements related to credit completion, the scholarship increased credit completion among low-achieving students. Some students appear to manipulate scholarship eligibility by taking fewer courses or strategically dropping courses during a qualifying semester in order to secure aid. A bounding exercise suggests partial manipulation of eligibility rules results in selection bias which underestimates the true effect of the scholarship on time to degree and credit completion.
Keywords: C14; D04; I22; I23; H75; 330; higher education; state merit scholarships; time to degree; college completion